2021
DOI: 10.3390/pr9091621
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on Heat Transfer Efficiency of Regenerative Thermal Oxidizers with Three Canisters

Abstract: The heat transfer efficiency of a regenerative thermal oxidizer with three canisters used for volatile organic compounds treatment was studied using numerical simulation methods. A one-dimensional model that took into account the variation of physical parameters with temperature was built. The results show that the preheating temperature and outlet temperature tend to be stable as the operation time is increased. The heat transfer efficiency of equipment was mainly evaluated by heat recovery efficiency and ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…This is also accompanied by a drop in the heat release ratio from 89.9% to 62.2%. This conclusion is consistent with those of Pu et al [43], who demonstrated that an increase in the height of the heat storage increases the heat transfer efficiency of the system. A comparison of Figures 10 and 11 implies that the synergistic effect of methane oxidation efficiency and the heat storage/release ratio from the regenerator determines the thermal and stability performances of the system.…”
Section: Effect Of Chamber/regenerator Height Ratiosupporting
confidence: 93%
“…This is also accompanied by a drop in the heat release ratio from 89.9% to 62.2%. This conclusion is consistent with those of Pu et al [43], who demonstrated that an increase in the height of the heat storage increases the heat transfer efficiency of the system. A comparison of Figures 10 and 11 implies that the synergistic effect of methane oxidation efficiency and the heat storage/release ratio from the regenerator determines the thermal and stability performances of the system.…”
Section: Effect Of Chamber/regenerator Height Ratiosupporting
confidence: 93%
“…The research on the regenerative chamber was also extended to the entire cuboid-shaped RTO. Although its average thermal efficiency could reach 90%, the residence time in each period within the oxidation chamber varied greatly, resulting in a nonuniform distribution of velocity and temperature within the oxidation chamber. , This was due to the odd number of regenerative chambers and cuboid-shaped oxidation chamber. The different intake and exhaust regenerative chambers at different periods resulted in differences in the gas flow paths.…”
Section: Introductionmentioning
confidence: 99%
“…The volatile organic compounds (VOCs) emitted into the environment accounted for one-third of the total pollutant emissions in industry [1]. Currently, common methods for the recovery and treatment of VOCs include adsorption, solution absorption, photocatalytic oxidation, and hightemperature oxidation [2][3][4].…”
Section: Introductionmentioning
confidence: 99%